Java EE web application primer : building Bullhorn : a messaging app with JSP, Servlets, JavaScript, Bootstrap and Oracle - Wolf, Dave; Henley, A. J. (Apress, 2017)
Build an online messaging app using Java Servlets, JSP, Expression Language, JSTL, JPQL, Sessions/Cookies, HTML/CSS/JavaScript, and the Bootstrap framework. This book explains Java EE, along with its associated technologies making it perfect for those with at least basic programming experience in Java or C. Java EE Web Application Primer teaches you how to develop complete web applications using Oracle as the database. By the end of the book you will have developed an online messaging app like Twitter. From there you can create other applications such as an online survey tool. You will: Build a Twitter-like web application called Bullhorn using Java, Oracle, and more Create web applications using Eclipse Design web pages with HTML forms, tables, and more Use SQL along with Java and Oracle for database accessibility Connect to a database using the Java Persistence APIs Create dynamic web pages with JavaScript, JSP, and the tag libraries Get web pages to stand out with Bootstrap, jQuery, and CSS.